The Hidden Aspects of American Democracy - Bouazid, Tayeb (Journal of Legal Studies and Researches, 2022)
The United States has had a greater impact on the world, for better or for worse. Its involvement in democracy promotion has attracted such great attention, together with a good deal of skepticism and suspicion. The building blocks of U.S. democracy promotion have come into question after September 11, 2001 where the pursuit of democracy promotion policy historically has served US national self-interests. This paper argues that placing U.S. democratic ideals in a secondary rank to geopolitical concerns along with the tendency to promote US-style democracy resulted in ideological polarization within America and many other countries-a conflict created by the US that is hard to assimilate by the Arabs.